A three-stage exercise-oriented problem-based learning model for double-weak students in applied undergraduate education - Huang, Xianbin; Hu, Yao; Chen, Liming (Frontiers in Education, 2025)
In the context of mass higher education, Chinese application-oriented undergraduate institutions face significant teaching challenges stemming from the increasingly diverse student population. This study focuses on a representative group of “double-weak” students—learners with weak academic foundations and limited mathematical-logical skills in high school. Empirical research reveals that the traditional Project-Based Learning (PBL) model exhibits adaptability issues, such as insufficient foundational skill support and low knowledge transfer efficiency. To address these challenges, this study proposes an innovative “Exercise-Oriented” (E-O) instructional improvement framework, establishing a “three-stage progressive spiral” PBL improvement model. The model consists of: (1) Basic Computation Reinforcement Layer, which restructures mathematical cognitive systems through structured exercises; (2) Application and Practice Transition Layer, which facilitates the targeted transfer of knowledge to practical competencies through engineering case studies; and (3) Modeling and Innovation Expansion Layer, which fosters complex problem-solving abilities through open-ended problem scenarios. A one-semester teaching experiment demonstrated that the E-O-driven approach led to a 5.75% improvement in basic computational skills, an 8.25% increase in teamwork abilities, and a 9.80% enhancement in innovative thinking compared to the control group. This research not only provides a new paradigm for the localization of PBL theory but also contributes a Chinese solution to global research on development pathways for students with weak academic foundations. The findings have significant theoretical value and practical implications for promoting educational equity and improving teaching quality.